2020
DOI: 10.3390/life10070101
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Oxidative Stress and Misfolded Proteins in the Mechanism of Neurodegeneration

Abstract: Aggregation of the misfolded proteins β-amyloid, tau, huntingtin, and α-synuclein is one of the most important steps in the pathology underlying a wide spectrum of neurodegenerative disorders, including the two most common ones—Alzheimer’s and Parkinson’s disease. Activity and toxicity of these proteins depends on the stage and form of aggregates. Excessive production of free radicals, including reactive oxygen species which lead to oxidative stress, is proven to be involved in the mechanism of pathology in mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 109 publications
1
60
0
Order By: Relevance
“…In the current study, we found that oxidative stress specifically caused by the Aβ 1-42 -induced activation of NAD(P)H oxidase (NOX) underlies glucose metabolism deficiency. It was previously reported in multiple cell types that Aβ 1-42 induces brain oxidative stress (21), largely via activation of NOX (22)(23)(24). We show in vivo that NOX activation by oligomeric Aβ 1-42 results in pathological changes in brain glucose consumption, hippocampal network hyperactivity, and neuropsychiatric-like disturbances in the behavior of mice-all abnormalities that can be prevented by administration of the novel selective NOX2 antagonist GSK2795039.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…In the current study, we found that oxidative stress specifically caused by the Aβ 1-42 -induced activation of NAD(P)H oxidase (NOX) underlies glucose metabolism deficiency. It was previously reported in multiple cell types that Aβ 1-42 induces brain oxidative stress (21), largely via activation of NOX (22)(23)(24). We show in vivo that NOX activation by oligomeric Aβ 1-42 results in pathological changes in brain glucose consumption, hippocampal network hyperactivity, and neuropsychiatric-like disturbances in the behavior of mice-all abnormalities that can be prevented by administration of the novel selective NOX2 antagonist GSK2795039.…”
Section: Introductionmentioning
confidence: 53%
“…In that context, the likely source of the H 2 O 2 and actual trigger of seizures is the reactive oxygen species (ROS)-generating NAD(P)H oxidase (NOX) (32). Aβ 1-42 has been reported to induce oxidative stress in multiple cell types by activating NOX (21)(22)(23)(24). Therefore, we asked whether the toxic effect of Aβ on glucose metabolism was mediated by NOX activation.…”
Section: Aβ 1-42 Toxicity Is Prevented By Blockade Of Nox2mentioning
confidence: 99%
“…Neurodegenerative diseases, as diverse group ailments, are characterized by progressive loss of neuronal cells in the targeted brain regions [33]. The pathophysiology of neurodegeneration is not yet fully understood; however, elevated oxidative stress has been indicated as one of the major factors responsible for the degeneration of neuronal cells [34,35]. Elevated oxidative stress may induce cellular damage, impair the DNA repair system, and trigger mitochondrial apoptosis, all of which are likened with aging and neurodegeneration [36,37].…”
Section: Pathological Bases Of Oxidative Stress and Neuroinflammationmentioning
confidence: 99%
“…For instance, a slow conversion of early, easy-degradable aggregates into compact, highly structured oligomers was detected in α-synuclein fibrillization [13], which is related to the progress of Parkinson's disease. These later oligomers induce much higher levels of reactive oxygen species (ROS) in cells than do earlier oligomers [14]. While focusing on Aβ aggregation, these oligomers interact with lipid membrane surfaces through weak electrostatic interactions that promote conformational transition from α-helix structures to β-sheet conformations [15].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been observed that Aβ alters membrane phospholipid fluidity through its own insertion into lipid bilayers [16]. That insertion, in form of pores, induces calcium-signaling, activating NADPH oxidase, stimulating nitric oxide production, and finally leading to increased oxidative stress and to neurodegeneration [14,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%